Green Transformational Leadership for Addressing Global Business Challenges through Sustainable Green Management - Tetty Sufianty Zafar; Abdul Bari; Deni Muhammad Danial; Wandy Zulkarnaen (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Increasing environmental pressures and sustainability demands have compelled organizations to adopt green management practices as a strategic response to global business challenges. This study explores the role of green transformational leadership in promoting green management to face global business challenges, and examines its influence on Green Human Resource Management (GHRM), sustainability innovation, and environmental performance. Using a qualitative case study design in five Indonesian multinational companies, data were collected from 22 participants (president directors, human resource directors, sustainability managers, line managers), two FGDs, and documentation. The Gioia methodology with a thematic approach was used for analysis. Findings show that green transformational leadership catalyzes green transformation through green vision, intellectual stimulation, pro-environmental modeling, and individual attention. GHRM practices (recruitment, training, performance, compensation, green participation) translate leadership vision into employee behavior. Sustainability innovation mediates the relationship between GHRM and environmental performance. Top management commitment and organizational social capital strengthen green practices as contingency factors. This study develops an integrated green transformational leadership model with a dual-pathway mechanism. It guides corporate leaders in articulating a green vision and human resource managers in designing integrated GHRM systems. Policy-wise, it recommends strengthening GHRM regulations and incentives for green companies.